Oral Contraceptive Use and Increased Risk of Stroke: A Dose–Response Meta-Analysis of Observational Studies - Li, Feng; Zhu, Lin; Zhang, Jie; He, Hongye; Qin, Yueqi; Cheng, Yuan; Xie, Zongyi (Frontiers in Neurology, 2019)
Background: Oral contraceptive (OCP) use might increase the risk of stroke in women. We examined a possible dose–response relation between OCP use and the risk of stroke in young and middle-aged women. Methods: A retrieval of PubMed and EMBASE databases was performed. We selected observational studies that reported odds ratios (ORs) with 95% confidence intervals (CIs) for the risk of stroke in OCP users. A two-stage dose–response analysis was conducted using the random-effects model and the restricted spline model. Results: A total of 6 cohort studies and 12 case–control studies were included, which involved 2,143,174 participants and 11,661 cases of stroke including ischemic stroke (IS), hemorrhagic stroke (HS), and stroke of unknown origin. The pooled ORs of total stroke were 1.19 (95% CI, 1.16–1.23) for every 10-μg increment in estrogen dosage, 1.20 (95% CI, 1.05–1.37) for every 5-years increment in duration of OCP use, and 0.82 (95% CI, 0.68–0.98) for every 5-years increment in duration of OCP cessation. The ORs of IS were 1.20 (95% CI, 1.17–1.22) in estrogen dosage, 1.24 (95% CI, 1.04–1.49) in duration of OCP use, and 0.78 (95% CI, 0.67–0.92) in duration of OCP cessation. The ORs of HS were 1.10 (95% CI, 1.04–1.16) in estrogen dosage, 1.13 (95% CI, 0.93–1.36) in duration of OCPs, and 0.71 (95% CI, 0.55–0.92) in duration of OCP cessation. The pooled ORs of total stroke from prospective studies (1.12; 95% CI, 1.01–1.24) were lower than those from retrospective studies (1.30; 95% CI, 1.01–1.67). Conclusions: The higher estrogen dosage significantly increased the risks of total stroke, IS, and HS, respectively. The longer duration of OCP use significantly increased the risks of total stroke and IS, but its effects on HS risk were marginal. The longer duration of OCP cessation significantly decreased the risks of total stroke, IS, and HS, respectively. These findings affirm the contribution of estrogen dose and duration of OCP use to the increased risk of stroke, which may be critical for the instruction of OCP use and the prevention and management of cerebrovascular diseases.